Photograph of shore birds feeding on a pond - Rosene, Walter M., Sr., 1880-1941et al
A flock of approximately 250 shore birds feeding on the Kirkendall Pond, May 24, 1925. The flock included eight Red-backed Sandpipers, three Semipalmated Plovers, Least Sandpipers, Semipalmated Sandpipers, Wilson's Phalarope, and one Stilt Sandpiper. Photograph originally titled "Shore birds feeding on pond." Rosene provides details on back of photograph. Epson--sheet feed/flatbed